CP Violation - Branco, Gustavo (Oxford University Press, 1999)
The violation of charge-conjugation and parity symmetries is a leading area of research in particle and nuclear physics, with important implications for understanding the generation of matter in the universe. CP violation occurs during the decay of the elementary particles known as kaons and the process remains little understood. This book provides a self-contained introduction to CP violation. It outlines the underlying theory and related experiments, taking a systematic approach.